2017
DOI: 10.1161/strokeaha.116.013977
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone for Secondary Stroke Prevention

Abstract: Background and Purpose-Pioglitazone reduced major vascular events after ischemic stroke in a recent randomized controlled trial. The purpose of this study was to conduct a meta-analysis of randomized controlled trials to evaluate the effect of pioglitazone therapy in reducing the risk of recurrent stroke in stroke patients. Methods-Pubmed, EMBASE, Medline, and Cochrane Central Register of Controlled Trials from 1966 to March 2016 were searched to identify relevant studies. We included randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 34 publications
2
46
0
1
Order By: Relevance
“…12 In a meta-analysis of studies in patients with stroke and insulin resistance, prediabetes, and diabetes mellitus, pioglitazone was associated with a 42% lower risk of recurrent stroke. 13 Adverse events that were more common in individuals using pioglitazone in the IRIS trial included weight gain, edema, and bone fractures.…”
mentioning
confidence: 99%
“…12 In a meta-analysis of studies in patients with stroke and insulin resistance, prediabetes, and diabetes mellitus, pioglitazone was associated with a 42% lower risk of recurrent stroke. 13 Adverse events that were more common in individuals using pioglitazone in the IRIS trial included weight gain, edema, and bone fractures.…”
mentioning
confidence: 99%
“…In the Diabetes Prevention Program, metformin significantly reduced the myocardial infarction events in prediabetic patients and this effect persisted for a 10-year follow-up [ 19 , 66 ]. Furthermore, the IRIS trial found that patients with insulin resistance receiving pioglitazone had a reduced risk of stroke or myocardial infarction [ 67 ]. Recent studies suggested that metformin has a direct anti-inflammatory action independent of improvement of metabolic parameters (hyperglycemia and insulin resistance) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of three other meta-analyses on the effects of pioglitazone on CVD in randomized–controlled trials (RCTs), are supportive to our results in their conclusion that pioglitazone has protective effects on CVD. However the effects of pioglitazone on HF were inconsistent among the studies, which may in part be explained by differences in the study populations [ 37 39 ]. In contrast to these previous meta-analyses, we studied the effects of pioglitazone on cardiovascular events in a specific population of patients with a history of CVD, thereby not restricting our study to patients with insulin resistance, pre-diabetes or diabetes mellitus type 2 (T2DM).…”
Section: Discussionmentioning
confidence: 99%